The health aspects of hydrocolloids - Edwards, Christine; Garcia, A. (Elsevier Inc., 2009)
© 2009, Woodhead Publishing Limited. All rights reserved.The health effects of hydrocolloids are dependent on how they are incorporated into food. The contribution of each hydrocolloid is small and the health benefits of these compounds cannot be separated from those of other non-digestible carbohydrates. The impact of hydrocolloids on gastric emptying and small intestinal digestion and absorption is well established. More recent work has explored new sources and their mechanisms of action related to their fermentation to short chain fatty acids and their impact on the intestinal microbiota along with potential actions the short chain fatty acids may have on plasma lipids and satiety. This is of increasing importance given the current global epidemic in obesity.